2022
DOI: 10.1021/acssuschemeng.2c03373
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Molecular Simulation Strategies for Understanding the Delignification Mechanism of Biomass in Cyrene

Abstract: In recent years, the cellulose-derived solvent Cyrene has piqued considerable interest in the green chemistry community despite only recently being available in the quantities required for solvent applications. Deconstruction of cellulose is an essential step in the production of fuel and value-added chemicals from lignocellulosic biomass. However, the high recalcitrance and heterogeneity of lignin hinder this process, necessitating the need to solubilize lignin. To understand the dissolution of lignin in Cyre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…By performing the quantum chemical calculations, the most stable conformer of lignin structure was obtained and used in the COSMO-RS calculations. The same chemical structure and stable conformer was used in our previous COSMO-RS calculations for lignin in amines, Cyrene, and protic ILs, and the results are in good agreement with experimental lignin solubility 8 , 63 , 64 .…”
Section: Resultssupporting
confidence: 72%
“…By performing the quantum chemical calculations, the most stable conformer of lignin structure was obtained and used in the COSMO-RS calculations. The same chemical structure and stable conformer was used in our previous COSMO-RS calculations for lignin in amines, Cyrene, and protic ILs, and the results are in good agreement with experimental lignin solubility 8 , 63 , 64 .…”
Section: Resultssupporting
confidence: 72%
“…In this work, we analyzed structure–solubility relationships between lignin pentamers and organic solvents across a large space of possible lignin/solvent compositions. As a metric predicting solubility, we calculated infinite dilution activity coefficients (ln­(γ)) for 28 lignin pentamers in 50 organic solvents using COSMO-RS, which have been shown to predict experimental trends in lignin solubility. , ,,, We then parameterized a regression model to predict ln­(γ) values as a function of five parameters: three parameters describing the solvent and two parameters describing the S- and H- contents of the lignin. We used Kamlet–Taft ( K – T ) parameters to identify solvents based on their proticity (α), basicity (β), and polarity (π).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used empirical parameters, such as Hansen solubility parameters, to guide solvent selection for fractionation, but these parameters do not capture variations in lignin composition. Recent computational studies using conductor-like screening model for realistic solvents (COSMO-RS) calculations or molecular dynamics (MD) simulations have also explored the molecular basis of lignin solubility but generally for a small range of lignin structures/solvents due to their computational expense. There, thus, remains a need for methods to efficiently guide solvent selection for lignin solubilization while accounting for the heterogeneous population of possible lignin structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49] Recent work by Mohan et al provided an account of lignin-Cyrene and lignin-Cyrene : water interactions using a combination of COSMO-RS and all-atom molecular dynamics simulations and suggested that Cyrene has a preferential interaction with lignin when in mixtures with water and caused isolated lignin chains to adopt randomcoil like conformation. 50 However, the prior work made use of non-optimized force-field for Cyrene obtained from CGenFF, modelled a generic lignin, did not consider inter-lignin chain interactions, i.e. the behaviour of lignin aggregates, and performed MD simulations of only two of the experimental ratios considered here.…”
Section: Papermentioning
confidence: 99%